Boom for whom? : education, desegregation, and development in Charlotte - Smith, Stephen Samuel, 1942- (State University of New York Press, 2004)
"Bringing a new perspective to Charlotte's landmark school desegregation efforts, Stephen Samuel Smith provides a history of the nationally-praised mandatory busing plan and the court battle that led to its ultimate demise. Although both black and white children benefited from busing, its most ongoing consequences were not educational, but the political and economic ones that served the interests of Charlotte's business elite and facilitated the city's economic boom. Drawing on urban regime theory, Smith shows how busing enhanced civic capacity and was part of a political alliance between Charlotte's business elite and black political leaders. This account of Charlotte's history has national implications for desegregation, urban education, efforts to build civic capacity, and the political involvement of the urban poor."--Jacket